Pengaturan Outsourcing Pasca Undang-undang Nomor 6 Tahun 2023 dan Putusan Mahkamah Konstitusi Nomor 168/PUU-XXI/2023 - Pranoto, Tri Wahyu; Mbunai, La Ode; Bahari, Syaiful; Suparman, Yusup (Universitas Sains Indonesia Publishing, 2025)
The regulation of outsourcing in Indonesian labor law has undergone significant changes following the enactment of Law Number 6 of 2023 on Job Creation, which permits outsourcing practices without explicitly limiting the types of work that may be outsourced. This development raises juridical concerns, particularly with regard to legal certainty in employment relationships and the protection of workers’ rights. In this context, Constitutional Court Decision Number 168/PUU-XXI/2023 is of particular importance, as it affirms the constitutional boundaries in the formulation and implementation of labor law norms.This study aims to analyze the juridical implications of outsourcing regulation following the enactment of Law Number 6 of 2023 based on constitutional principles as articulated in Constitutional Court Decision Number 168/PUU-XXI/2023. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that the regulation of outsourcing is conditionally constitutional, meaning that its validity is contingent upon the existence of normative limitations to ensure legal certainty and the protection of workers’ rights. A key juridical implication of the decision is the emergence of a constitutional obligation for the minister responsible for labor affairs to regulate outsourced work restrictively through implementing regulations in order to safeguard the constitutional rights of workers.